ASSESSING THE CUMULATIVE IMPACTS OF HYDROPOWER REGULATION ON THE FLOW CHARACTERISTICS OF A LARGE ATLANTIC SALMON RIVER SYSTEM. (5th April 2013) - Birkel, C.; Soulsby, C.; Ali, G.; Tetzlaff, D.
ABSTRACT We assessed the influence of hydropower on the flow characteristics of the river Tay, one of the UK's most heavily regulated catchments and important Atlantic salmon fisheries. Hydropower developments in the mid‐20th century preceded flow data collection, resulting in knowledge gaps over how far regulated flows deviate from natural and how ecosystem functioning might have been impacted. We used 29 unregulated catchments in and around the Tay to assess the relationships between hydroclimatic conditions, landscape structure and the overall flow regime, as well as the annual, monthly and daily flow metrics. This allowed the identification of flow characteristics by using an integrated suite of regression approaches (nonlinear, MLR and random forests) to assess likely impacts at 11 regulated sites. The results showed that the impacts of regulation are highly variable in both space and time. Headwater sub‐catchments are most heavily affected, and water imports or exports as part of hydropower schemes can increase or decrease annual runoff by up to 50%, respectively. On a monthly basis, regulation primarily increased summer low flows; winter high flows increased in catchments affected by water imports and reduced where there was a net water export. At larger catchment scales, impacts were relatively small, as unregulated tributaries re‐naturalize the flows and the effects of intra‐basin transfers balance. Non‐stationarity in climate and water use in the catchment dictates that adaptive management of flows may be necessary to protect ecosystems services. Copyright © 2013 John Wiley & Sons, Ltd.